Main content

### Course: 8th grade > Unit 4

Lesson 3: Solving systems with substitution- Systems of equations with substitution: 2y=x+7 & x=y-4
- Systems of equations with substitution
- Systems of equations with substitution: y=4x-17.5 & y+2x=6.5
- Systems of equations with substitution: -3x-4y=-2 & y=2x-5
- Systems of equations with substitution: 9x+3y=15 & y-x=5
- Systems of equations with substitution
- Systems of equations with substitution: y=-5x+8 & 10x+2y=-2
- Systems of equations with substitution: y=-1/4x+100 & y=-1/4x+120
- Substitution method review (systems of equations)

© 2024 Khan AcademyTerms of usePrivacy PolicyCookie Notice

# Systems of equations with substitution: y=4x-17.5 & y+2x=6.5

Learn to solve the system of equations y = 4x - 17.5 and y + 2x = 6.5 using substitution. Created by Sal Khan and Monterey Institute for Technology and Education.

## Want to join the conversation?

- What if the problem is

-5x + y= -2

-3 + 6y= -12

How would I figure out either the x value first or the y value first ?(4 votes)- You were already given the Y value, look:

-5x + y = -2 -3 + 6y = -12

y = -2 + 5x 6y = -9

y = -9/6

y = -3/2 <--- this is your Y value

Y = -9/3 (which is the same as -3/2), all you have to do to solve for X is substitute your Y value into the equation: -5x + 7 = -2

Here it goes:

-5x - 2/3 = -2

-5x = -2 +(2/3)

-5x = -4/3

x = (-4/3(6 votes)

- Are you supposed to use the substitution method whenever you see the systems of equations?(4 votes)
- Systems of equations can be solved by graphing, elimination, or substitution. Which one you use comes down to the systems of equations you're solving for, and how much work you want to do. Some systems solve easier using elimination, while others solve quickly using substitution.(4 votes)

- how would you solve this problem

x+y+7z=21

x+y+9z=29

x+y+4z=39(4 votes)- If you subtract the first one from the second one, you find that z = 4.

If you subtract the third one from the second one, you find that z = -2.

So, those equations don't have a solution.(2 votes)

- How long does it take to learn this?(4 votes)
- How does this apply to real life @_@(2 votes)
- hi! sometimes, yes, you can't see why/how math applies to real life. and that is normal! you definitely may use it in the future, whether it be for your profession, or maybe financial purposes! either way, it is important. you also may need it for higher math classes, such as algebra. these are the fundamentals of math classes in your future.(4 votes)

- What's up guys(3 votes)
- the sky is up (or the roof)(2 votes)

- how do i solve this

2x-3y=-24

x+6y=18(2 votes)- Try watching Sal's videos again before reading on.

Convert either of the equations into the form x = a*y + b or y = c*x + d

Substitute the value for x (or y) in the other equation

Solve this equation

Plug the result into either of the original equations

Solve that

Voila

So you could start by converting

x + 6y = 18

into

x = -6y + 18

Plug that into 2x - 3y = -24

2*(-6y + 18) - 3y = -24

Multiply into brackets

-12y + 36 - 3y = -24

Solve this equation for y

Plug the result into x = -6y + 18 to get x(3 votes)

- What would I do if there is a number in front of the y?

Like:

y=6x-11

-2x-3y=-7

What would y first step be?

Would the combined equation look like:

-2x-3(6x-11)=-7 ?(2 votes)- If you have

y=6x-11

-2x-3y=-7

and you want to solve by substitution, you can just substitute 6x-11 into the second equation everwhere you see a y

like this

-2x - 3(6x-11) = 7 Then distribute the -3 so

2x + ((-3)*6x) + ((-3)*(-11)) +33 = 7

-2x -18x +33 = 7

Does that help make it click for you.(3 votes)

- 2x-3y=15

x-2y=16

What video do I watch to find out how to solve an equation like this one? Help(2 votes)- MusicGrl,

This video is solves a system of equations very similar to your equations.

https://www.khanacademy.org/math/cc-eighth-grade-math/cc-8th-systems-topic/cc-8th-systems-with-substitution/v/solving-systems-by-substitution-3(3 votes)

- The problem is 840=(x+y) eq.1 & 840=(y-x)7 need to understand how to solve in substitution method HELP?(3 votes)

## Video transcript

We have this system of
equations, y is equal to 4x minus 17.5, and y plus
2x is equal to 6.5. And we have to solve
for x and y. So we're looking for x's
and y's that satisfy both of these equations. Now, the easiest way to think
about it is we've already solved for y in this
top equation. Let me write it again. I'll write it in pink. We have y is equal
to 4x minus 17.5. So this first equation is
telling us, literally, by this constraint, y should be
4 times x minus 17.5. Now, the second equation says
whatever y is, we had 2 times x, and that should be 6.5. Well, the y here also has to
meet this constraint up here. It also has to meet the
constraint that it has to be 4 times x minus 17.5. So what we can do is, is we can
substitute this value for y into this equation. Let me be clear what
I'm doing. The second equation here is
y plus 2x is equal to 6.5. We know that y has to be equal
to this thing right here. y has to be equal to
4x minus 17.5. So let's take 4x minus 17.5,
and substitute y with that. So let's put that right there. So if we were to do that, if we
were to replace this y with 4x minus 17.5, because that's
what the first equation is telling us, then we get
4x minus 17.5, plus 2x is equal to 6.5. And now we have a single linear equation with one unknown. Let's solve for x. So first we have our x
terms. We have a 4x, and we have a 2x. We can group them or
add them together. 4x plus 2x is 6x. And then we have 6x minus
17.5 is equal to 6.5. Then we can get the 17.5 out
of the way by adding it to both sides of the equation. So this is negative 17.5, so
let's add positive 17.5 to both sides of this equation. And we are left with the
left-hand side is just going to be 6x, because these
guys cancel out. 6x is going to be equal to--
and 6.5-- see, 6 plus 17 is 23, and then 0.5
plus 0.5 is 1. So this is going to be 24. And then we can divide both
sides of this equation by 6. And you are left with x is equal
to 24 over 6, which is the same thing as 4. So we figured out the x value
for the x and y pair that satisfy both of these
equations. Now we need to figure
out the y value. And we can do that by taking
this x and putting it back into one of these equations. We can do it in to either one. We should get the
same y value. So let's just do this
top one up here. So if we assume x is equal to 4,
this top equation tells us y is equal to 4 times x, which
in this case is 4, minus 17.5. Well, this is equal to 16 minus
17.5, which is equal to negative 1.5. So y is equal to negative 1.5. So the solution to this system
is x is equal to 4, y is equal to negative 1.5. And you can even verify that
these two, they definitely work for the top one if you put
4 times 4, minus 17.5, you get negative 1.5. But they also work for
the second one. And let's do that. In the second one, if you take
negative 1.5, plus 2 times x-- plus 2 times 4-- what
does that equal? That's negative 1.5 plus 8. Well, negative 1.5
plus 8 is 6.5. So this x and y satisfy both
of these equations.